ORGANIZATIONAL STRUCTURE OF NATIONAL AND INTERNATIONAL LEADING ORGANIZATIONS IN KYUDO (Physical Culture and Sport: Scientific Perspective, 2023)
The article reveals ways of organizing the traditional, national sport - kyudo in the world and in Japan. The relevance of the research lies in establishing the structure, organizational features, the impact of various forms of kyudo on the functioning of kyudo governing bodies.The purpose of the work is to substantiate the model of the structural organization of kyudo in Japan and the world and to identify common and distinctive features with the corresponding organization of Olympic archery.Results and conclusions.Diagrams of the organizational structures of Olympic archery and kyudo in Japan have been constructed. Common structural elements of both models are belonging to the International Federations of the respective sport, the Japan Sport Association (JSPO), the Japan Olympic Committee, the Japan Sports Agency (JSA), cooperation with the Japan Sports Promotion Center. They also include city, district, and prefectural organizations, various clubs, and the AllJapan High School Athletic Federation.The difference in the schemes concerns the cooperation of the Japan Paralympic Archery Federation with the All Japan Archery Federation, as well as its subordination to the All Japan Student Archery Federation. In the organizational structure of kyudo in Japan, there are no connections to the Paralympic sports, student organizations work independently. It includes traditional schools of ryu. Moreover, the main difference concerns belonging of the All Japan Kyudo Federation to the Martial Arts Council.It has been established that there are 50 national kyudo federations in the world, which are based in countries on all continents of the world, which in turn led to the creation of continental associations. Among all national organizations, only 28 participating countries are members of the International Kyudo Federation.
Keywords: kyudo; budo; national sport; traditions; Japan